SaaS-model-based approach for mobile government security. (1st October 2010) - Zhuo, Jun; Wei, June; Chen, Liangliang; Li, Zhibo
Mobile government is playing a more and more important role in the government information and service delivery to businesses and citizens. However, there are still many problems in the development of mobile government such as security and privacy, low cost-effective, redundant construction and low utilisation. This paper aims at providing a new Software-as-a-Service (SaaS)-model-based approach to solve some major problems in mobile government; and thereby, integration of SaaS with mobile government will proceed more smoothly. Directions for further research are presented, and academic and practical implications stemming from this study are also discussed.